Influence of scientific achievements of Professor Alicja A. Jaruga on development of selected re-search trends - Joanna Stępień - Andrzejewska (Zeszyty Teoretyczne Rachunkowości)
The purpose of this article is to highlight the importance of scientific achievements of Professor Alicja A. Jaruga. Presentation of her work is divided according to areas of interest, which include management accounting and cost accounting, financial accounting, accounting harmonization, public sector accounting and accounting history. For each of these areas the most important publications are presented and the number of citations is given. The paper also reviews the most important translations prepared under the guidance of prof. A. Jaruga. Publish or perish program 4 was used in the analysis.